Development and testing of invasion-associated DNA probes for detection of Shigella spp. and enteroinvasive Escherichia coli. - Venkatesan, M (1988)
Genetic determinants of the invasive phenotype of Shigella spp. and enteroinvasive Escherichia coli (EIEC), two common agents of bacillary dysentery, are encoded on large (180- to 210 kilobase), nonconjugative plasmids. Several plasmid-encoded antigens have been implicated as important bacterial ligands that mediate the attachment and invasion of colonic epithelial cells by the bacteria. Selected invasion plasmid antigen (ipa) genes have recently been cloned from Shigella flexneri serotype 5 into the lambda gt11 expression vector. Portions of three ipa genes (ipaB, ipaC, and ipaD) were tested as DNA probes for diagnostic detection of bacillary dysentery. Under stringent DNA hybridization conditions, all three DNA sequences hybridized to a single 4.6-kilobase HindIII fragment of the invasion plasmids of representative virulent Shigella spp. and EIEC strains. No hybridization was detected in isogenic, noninvasive Shigella mutants which had lost the invasion plasmid or had deleted the ipa gene region. Furthermore, these probes did not react with over 300 other enteric and nonenteric gram-negative bacteria tested, including Salmonella, Yersinia, Edwardsiella, Campylobacter, Vibrio, Klebsiella, Aeromonas, Enterobacter, Rickettsia, and Citrobacter spp. and various pathogenic E. coli strains. The use of unique invasion-essential gene segments as probes for the specific detection of invasive dysentery organisms should benefit both epidemiologic and diagnostic analyses of Shigella spp. and EIEC.